2020
DOI: 10.1111/liv.14468
|View full text |Cite
|
Sign up to set email alerts
|

The global epidemiology of hepatitis E virus infection: A systematic review and meta‐analysis

Abstract: Background and aims Hepatitis E virus (HEV), as an emerging zoonotic pathogen, is a leading cause of acute viral hepatitis worldwide, with a high risk of developing chronic infection in immunocompromised patients. However, the global epidemiology of HEV infection has not been comprehensively assessed. This study aims to map the global prevalence and identify the risk factors of HEV infection by performing a systematic review and meta‐analysis. Methods A systematic searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 46 publications
7
134
1
Order By: Relevance
“…The global burden of human infection caused by zoonotic HEV strains is currently estimated to be 10 million symptomatic cases annually (Li et al., 2020). In Switzerland, hepatitis E is a notifiable disease since 2017, with an annual incidence of 1.32 per 100’000 inhabitants reported in 2019 (Swiss Federal Office of Public Health, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The global burden of human infection caused by zoonotic HEV strains is currently estimated to be 10 million symptomatic cases annually (Li et al., 2020). In Switzerland, hepatitis E is a notifiable disease since 2017, with an annual incidence of 1.32 per 100’000 inhabitants reported in 2019 (Swiss Federal Office of Public Health, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies on HEV burden have expanded geographically over time, existing data are insufficient to identify temporal or geographic trends in risk. Similar to other reviews, we note challenges in interpreting and comparing data from different studies due to variability in diagnostic assays used, definitions of suspected and confirmed cases of HEV (160)(161)(162), and lack of standardized age groups used in analysis. Unified guidance and best practices for measuring disease burden and risk factors are urgently needed to generate evidence needed for developing a global strategy for hepatitis E control.…”
Section: Discussionmentioning
confidence: 57%
“…However, the choice of the HEV serology test might influence the results and may also explain different results of anti-HEV IgG antibody seroprevalences in different publications [23,24].…”
Section: Discussionmentioning
confidence: 99%